Comparing identification of clinically relevant Prevotella species by VITEK MS and MALDI biotyper - ÜLGER, NURVER (AKADEMIAI KIADO ZRT, 2019)
In this multicenter study, we aimed to evaluate the performance of MALDI Biotyper and VITEK MS, for identification of Prevotella species. Three hundred and fourteen clinical isolates, collected in eight European countries between January 2014 and April 2016, were identified at the collecting sites by MALDI Biotyper (versions 3.0 and 3.1) and then reidentified by VITEK MS (version 3.0) in the central laboratory. 16S rRNA gene sequencing was used as a standard method. According to sequence analysis, the 314 Prevotella strains belonged to 19 species. MALDI Biotyper correctly identified 281 (89.5%) isolates to the species level and 33 (10.5%) only at the genus level. VITEK MS correctly identified 253 (80.6%) isolates at the species level and 276 (87.9%) isolates at the genus level. Thirty-three isolates belonging to P. bergensis, P. conceptionensis, P. corporis, P. histicola, and P. nanciensis, unavailable in the VITEK MS 3.0 database, were resulted in genus level or no identification. Six Prevotella strains, belonged to P. veroralis, P. timonensis, and P. conceptionensis not represented in the MALDI Biotyper system database, were misidentified at the genus level. In conclusion, both VITEK MS and MALD1 Biotyper provided reliable and rapid identification. However, the permanent extension of the databases is needed.
Keywords: anaerobic bacteria; Prevotella; 16S rRNA gene sequencing; mass spectrometry; VITEK MS; MALDI Biotyper; DESORPTION-IONIZATION-TIME; FLIGHT MASS-SPECTROMETRY; TOF MS; ANAEROBIC-BACTERIA; ROUTINE IDENTIFICATION; MULTICENTER EVALUATION; SYSTEM